Rise of a New Era: Strengthening of Indian Agriculture by Virtue of Agribusiness Incubation - Bhooshan, Neeru; Sharma, Akriti (Indian Farming, 2020)
Agriculture is considered as a noble profession in our country since ages. The farming activity had always been enterprising by its nature of providing a scope for innovation in terms of practices adopted or the resources used. Agricultural research and innovation had been making its mark since many years before the formal establishment of agricultural research system in the country. Since green revolution, it has taken its rapid pace and made India self-sufficient in food production. At the same time, many problems and challenges have also arisen that need serious attention i.e., soil degradation, agricultural waste, less availability of water for irrigation, postharvest losses and many others.